ACHIEVEMENT MOTIVATION AND ACADEMIC ACHIEVEMENT DIFFERENCESOF ENGLISH STUDENTS - RITA ERLINDA (Ta'dib, 2015)
This study was aimed at finding to find out whether there is any significant academic achievement difference of the fifth and seventh semester of English students based on their achievement motivation.This research used ex-post facto design. From data analysis using inferential statistics--T-test for independent samples with statistical analysis tool, SPSS 18, it was found that there was a significant academic achievement difference of the fifth semester of English students based on their achievement motivation. Conversely, there is no significant academic achievement difference of the seventh semester ofEnglish students based on their achievement motivation. It means that the level of achievement motivation did not contribute significantly on the level of students’ academic achievement.Key Words: Academic Achievement Differences, Achievement Motivation, English Students